PENDAMPINGAN DALAM STRATEGI PEMASARAN USAHA IKAN LELE UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI KELURAHAN SAKO BARU KECAMATAN SAKO KOTA PALEMBANG - Prihatini, Lishapsari; Aziz, Ervan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2020)
Assistance in the marketing strategy of the catfish business to improve the welfare of the community in the Sako Baru sub-district, Sako district, Palembang. Community assistance in the marketing strategy of the catfish business is a strategic step in improving the welfare of the community. This research was conducted in Kelurahan Sako Baru. In this study, data collection was carried out by means of observation, documentation and interviews regarding selected informants with the Catfish Business Assistance Program to Improve Community Welfare in Sako Baru sub-district. The results of this study indicate that (1) From the results of observations in the field, the authors conclude that community assistance through a marketing strategy assistance program for catfish business in Sako Baru sub-district, Sako District, Palembang City is quite good. (2) Human resources, in this case the government apparatus of Sako Baru sub-district, have tried hard enough in carrying out their duties in recording and verifying to assist the community or groups of catfish cultivators in Sako Baru sub-district in order to achieve the goals of community empowerment.